Study on Evaluating the Sustainability of Innovative Products - Lisha Geng; Jinge Xing; Zaojie Kong; Lixiao Geng; Haiyan Gao (Advances in Materials Science and Engineering)
In the process of product innovations, it is necessary to evaluate the sustainability of innovative products in order to meet the demands of sustainable development. So, the calculation process for evaluating the sustainability of innovative products is proposed in this paper. Firstly, the performances of the innovative products in social, economic, and environmental aspects are calculated based on the concepts proposed in this paper, including social matching degree, economic feasible degree, and environmental improving rate. Then, the vector-cosine method in the three-dimensional space is proposed to calculate the sustainability integrated in the three aspects, which regards innovative products as the vectors. Both the size and direction of the vectors are considered to calculate the sustainability. Finally, a case study of the cloud rail made by BYD Company in China is provided to illustrate the validity of the proposed calculation process.